2018
DOI: 10.1111/cup.13309
|View full text |Cite
|
Sign up to set email alerts
|

MART‐1‐labeled melanocyte density and distribution in actinic keratosis and squamous cell cancer in situ: Pagetoid melanocytes are a potential source of misdiagnosis as melanoma in situ

Abstract: Pagetoid melanocytes in AK and SCCIS should be interpreted with caution to avoid overdiagnosis of MIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The melanocyte confluence is defined in various studies as number of adjacent pigment cells without intervening keratinocytes. While in some reports neither pagetoid spread nor nesting of melanocytes was found, 5,22,28 in another study Melan-A staining could have suggested the presence of…”
Section: Melan-a/mart-1mentioning
confidence: 84%
See 3 more Smart Citations
“…The melanocyte confluence is defined in various studies as number of adjacent pigment cells without intervening keratinocytes. While in some reports neither pagetoid spread nor nesting of melanocytes was found, 5,22,28 in another study Melan-A staining could have suggested the presence of…”
Section: Melan-a/mart-1mentioning
confidence: 84%
“…The melanocyte confluence is defined in various studies as number of adjacent pigment cells without intervening keratinocytes. While in some reports neither pagetoid spread nor nesting of melanocytes was found, 5,22,28 in another study Melan‐A staining could have suggested the presence of these features in sun‐damaged skin 25 . Although transepidermal melanocytic migration may imply the diagnosis of melanoma, it is not an independent, unequivocal sign of this malignancy 40 .…”
Section: Immunohistochemical Detectability Of Melanocytes In Intraepi...mentioning
confidence: 96%
See 2 more Smart Citations
“…The narrow biological relationship among several SPSs may complicate the successful diagnosis of skin cancer. Certain researches have pointed out the difficulty in discerning among specific SPSs from the clinical, histological and molecular points of view: AK vs SCC [9], AK and SCC vs PRIMEL [10], SCC vs BCC and MSC [11], primary MCC (PMCC) vs metastatic MCC (MMCC) [12], etc. Different editions of the American Joint Committee on Cancer (AJCC) have gradually introduced the most outstanding clinical parameters for their diagnosis This work is licensed under a Creative Commons Attribution 4.0 License.…”
Section: Introductionmentioning
confidence: 99%